PLA composites reinforced with flax and jute fibers—A review of recent trends, processing parameters and mechanical properties - Sanivada, Usha Kiran (2020)
Multiple environmental concerns such as garbage generation, accumulation in disposal systems and recyclability are powerful drivers for the use of many biodegradable materials. Due to the new uses and requests of plastic users, the consumption of biopolymers is increasing day by day. Polylactic Acid (PLA) being one of the most promising biopolymers and researched extensively, it is emerging as a substitute for petroleum-based polymers. Similarly, owing to both environmental and economic benefits, as well as to their technical features, natural fibers are arising as likely replacements to synthetic fibers to reinforce composites for numerous products. This work reviews the current state of the art of PLA compounds reinforced with two of the high strength natural fibers for this application: flax and jute. Flax fibers are the most valuable bast-type fibers and jute is a widely available plant at an economic price across the entire Asian continent. The physical and chemical treatments of the fibers and the production processing of the green composites are exposed before reporting the main achievements of these materials for structural applications. Detailed information is summarized to understand the advances throughout the last decade and to settle the basis of the next generation of flax/jute reinforced PLA composites (200 Maximum).